Review of Veterinary Legislation for Prevention and Control of Infectious Diseases of Animals and its Situation in Nepal - Karki, S; Rana, S; Sharma, B.K.; Ghimire, N.P.; Chand, B.B.; Sharma, B; Bhatta, K; Pathak, P; Karki, N.P.S. (Nepalese Veterinary Journal, 2023)
Available within the full article